2013
DOI: 10.1158/0008-5472.can-12-4297
|View full text |Cite
|
Sign up to set email alerts
|

KEAP1 Is a Redox Sensitive Target That Arbitrates the Opposing Radiosensitive Effects of Parthenolide in Normal and Cancer Cells

Abstract: Elevated oxidative stress is observed more frequently in cancer cells than in normal cells. It is therefore expected that additional exposure to a low level of reactive oxygen species (ROS) will push cancer cells toward death, whereas normal cells might maintain redox homeostasis through adaptive antioxidant responses. We previously demonstrated that parthenolide enhances ROS production in prostate cancer cells through activation of NADPH oxidase. The present study identifies KEAP1 as the downstream redox targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 46 publications
3
41
0
Order By: Relevance
“…31 Indeed, ROS-mediated cell death is an essential base for radiotherapy and many chemotherapeutic treatments. 27,30 Although our investigation suggests that PL-mediated depletion of c-Met parallels a loss of viability of RCC cells, the direct impact of PL on the other important cellular pathways cannot be excluded. Our recent studies demonstrate that PL also potently inhibits NF-kB and Akt/mTOR signaling pathways in tumor cells of various origins.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…31 Indeed, ROS-mediated cell death is an essential base for radiotherapy and many chemotherapeutic treatments. 27,30 Although our investigation suggests that PL-mediated depletion of c-Met parallels a loss of viability of RCC cells, the direct impact of PL on the other important cellular pathways cannot be excluded. Our recent studies demonstrate that PL also potently inhibits NF-kB and Akt/mTOR signaling pathways in tumor cells of various origins.…”
Section: Discussionmentioning
confidence: 80%
“…This phenomenon can be explained, at least in part, by hyperactive metabolism and mitochondrial malfunction in malignant cells required for their rapid growth. 29,30 It has been suggested that a therapy designed to increase ROS to a level above the threshold for cancer cell death, but at an adaptable level for normal cells, would be an attractive strategy to selectively destroy cancer cells. 31 Indeed, ROS-mediated cell death is an essential base for radiotherapy and many chemotherapeutic treatments.…”
Section: Discussionmentioning
confidence: 99%
“…DMAPT and its parent compound parthenolide alkylate reactive cysteines on multiple protein targets including KEAP1 and inhibit canonical NF-κB signaling by interacting with IκB and the NFκBp65 subunit (47–49). In contrast to RTA 408, parthenolide or DMAPT reportedly did not inhibit cultured normal or immortalized prostate cells to the same extent as their malignant counterparts and this difference has been attributed to differential effects of DMAPT on KEAP1-dependent oxidation status in normal and malignant cells (46). This difference between RTA 408 and DMAPT suggests that tissue protection by RTA 408 as seen in vivo is not primarily due to cell-autonomous effects but likely depends on environmental factors provided by the tissue context in vivo.…”
Section: Resultsmentioning
confidence: 92%
“…We observed that topical application of RTA 408 markedly reduced radiation dermatitis in mice associated with significant increases in Nrf2 target genes and significant decreases in NF-kB target genes (45). Interestingly, radiation protection of normal prostate epithelial cells contrasted by growth inhibition of prostate cancer cells in vivo has been very recently described for dimethylamineparthenolide (DMAPT) (46). DMAPT and its parent compound parthenolide alkylate reactive cysteines on multiple protein targets including KEAP1 and inhibit canonical NF-κB signaling by interacting with IκB and the NFκBp65 subunit (47–49).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, with the protein kinase C-a inhibitor Ro317549 (Ro), parthenolide-mediated apoptosis inhibits expression and nuclear translocation of Nrf2, resulting in blockage of HO-1 expression. Parthenolide also stimulated oxidation of KEAP1 in normal prostate epithelial cells, leading to increased Nrf2 (NFE2L2) levels and subsequent Nrf2-dependent expression of antioxidant enzymes (84,85). Costunolide and CH2-BL induced HO-1 expression and Nrf2 nuclear accumulation in RAW264.7 macrophages (86).…”
Section: Nuclear Factor-related Factor 2 Signaling Pathwaymentioning
confidence: 99%